Michael Toolan, Narrative progression in the short story: first steps in a corpus stylistic approach (ENTHYMEMA, 2010)
Using tools derived from corpus linguistics, Toolan proposes some principles and techniques for a stylistic analysis which aims at the detection of textual elements that are responsible for reader's expectations and narrative prospection. A specific attention is given to one of this elements: the use of free indirect discourse. He wants to develop some criteria that allow a selection based only on lexical and sintactical data, in order to apply automated methods of searching to wide text corpora and test his theoretical. Here is the original article.